2018
DOI: 10.1016/j.infrared.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature of the foot: Reliability of infrared image analysis based in the angiosome concept

Abstract: Studies reporting the reliability of image analysis when assessing skin temperature of the foot are scarce. The aim of this study was to assess the interrater and intrarater reliability of the analysis of foot skin temperature based on the angiosome concept and the association between skin temperature differences and the differences in size of the ROIs. Methodology: Thermograms from 26 feet were analysed by two independent assessors and each assessor analysed the same images on different occasions. Mean temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Imaging heat radiation in the form of differences in the temperature distribution on the surface of the skin and the tissues situated deep in the body can provide information about the pathological changes [21,24]. Registered temperature changes are shown in the form of hot spots or areas of inhomogeneity in the curves [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging heat radiation in the form of differences in the temperature distribution on the surface of the skin and the tissues situated deep in the body can provide information about the pathological changes [21,24]. Registered temperature changes are shown in the form of hot spots or areas of inhomogeneity in the curves [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that the use of thermovision techniques is a very useful tool in the examination of patients. Thermovision techniques have been used for various purposes in medicine, including clinical testing of drugs [12], assessment of vascular reactions in hands [13][14][15][16][17][18], diagnosis of Raynaud's syndrome [19,20], evaluation of observational changes in osteoarthritis [9,15], detection of different kinds of tumors [21,22], and assessment of the skin condition in diabetic feet [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The camera was positioned perpendicular to the feet at 1 metre distance. Images were analysed with FLIR ResearchIR Max software (FLIR Systems, version 4.30.0.69) and regions of interest (ROI) were defined according to the angiosome concept (figure 1), which is a reliable methodology of infrared image analysis [10].…”
Section: Skin Temperature Assessmentmentioning
confidence: 99%
“…First, the number of pixels within the ROI was found to induce an inaccurate evaluation of T sk (Ring and Ammer 2000). The ROI selection was found to play a fundamental role in the reliability of IRT measurements (Ring and Ammer 2000, Seixas et al 2018. In fact, a relevant issue for biomedical IRT is the availability of tools for an objective comparison of images across different conditions or participants.…”
Section: Introductionmentioning
confidence: 99%